1966
DOI: 10.1139/t66-023
|View full text |Cite
|
Sign up to set email alerts
|

Yielding and Flow of Sand in Triaxial Compression: Part I

Abstract: A theoretical and experimental study of the nature of deformation of a sand sample when tested in the triaxial apparatus is presented. The medium is shown to be elastic-strain hardening plastic but does not conform to certain rules usually adopted in the classical theory of plasticity. Experimental verification of an earlier suggestion by Poorooshasb (1961) leads to a proof of the existence of a potential function, known as the plastic potential, of the form Ψ(σ, e) the parameters σ representing the stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(31 citation statements)
references
References 0 publications
1
28
0
2
Order By: Relevance
“…Then it is considered that deformation behavior is elastic under the yield point stress level and plastic over the yield point stress level. Studies on yielding of sand started from Poorooshasb et al (1966Poorooshasb et al ( , 1967, Scoˆeld and Wroth (1968) and Barden et al (1969) in earnest. Subsequently, Nishi and Esashi (1978) and Vermeer (1978) proposed a model considering yielding behavior accompanied by consolidation, and then Tatsuoka and Molenkamp (1983) discussed about yield surface considering coupling eŠect of consolidation and shear deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Then it is considered that deformation behavior is elastic under the yield point stress level and plastic over the yield point stress level. Studies on yielding of sand started from Poorooshasb et al (1966Poorooshasb et al ( , 1967, Scoˆeld and Wroth (1968) and Barden et al (1969) in earnest. Subsequently, Nishi and Esashi (1978) and Vermeer (1978) proposed a model considering yielding behavior accompanied by consolidation, and then Tatsuoka and Molenkamp (1983) discussed about yield surface considering coupling eŠect of consolidation and shear deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The ratios of the components of the increments of inelastic strain remain fairly constant along each radial or proportional (q/p = constant) loading path in stress space. Data presented by Poorooshasb et al (1966), Figure 3.8, and Tatsuoka (1972) substantiate this contention. Implicit in this premise is the existence of a radial, path-independent zero dilation line, and experimental studies by Kirkpatrick (1962) and Habib and Luong (1978) have confirmed the existence of such a line.…”
Section: The Inelastic Response In Subsequent Extension Testing Is Nomentioning
confidence: 71%
“…At a given stress point, the ratios of the components of the inelastic strain increments are the same for all outward loading paths through the point (Poorooshasb et al, 1966) …”
Section: The Inelastic Response In Subsequent Extension Testing Is Nomentioning
confidence: 99%
See 1 more Smart Citation
“…First, the conventional triaxial apparatus was largely used by Poorooshasb, et al [10], Poorooshasb, et al [11], Tatsuoka and Ishihara [12], Ishihara and Okada [13] and Vaid, et al [14], among others, used to investigate the effects of stress-induced anisotropy on the subsequent drained and undrained behaviour of dense sand. One of the objectives was to recognize the yield surface within the light of the elastoplasticity framework.…”
Section: Introductionmentioning
confidence: 99%